Clear cell myoepithelioma of the palate: a case report and comprehensive review - Anehosur, Venkatesh; Kotian, Divya B.; Anand, Jawahar; Kumar, Kiran; Kumar, Niranjan (International Surgery Journal, 2025)
Myoepitheliomas are a group of rare tumors of the salivary glands, primarily affecting the parotid gland. It accounts for less than 1% of all salivary gland tumors. The diagnosis of tumors of myoepithelial origin relies on evaluating the histologic features and is confirmed using immunohistochemical analysis. Vimentin and S-100 are non-specific but sensitive immunohistochemical markers of neoplastic myoepithelium. This is a unique case of a clear cell myoepithelioma of the hard palate. Diagnosis involved thorough histological examination and immunohistochemical confirmation, utilizing standard protocols. Our case showcases a rare occurrence of myoepithelioma, specifically the clear cell variant, in the hard palate. Histological analysis revealed large polyhedral cells with eosinophilic and clear cytoplasm and round to oval vesicular nucleus with small nucleoli. The cystic/ pseudo glandular spaces were filled with mucinous material. The results were further validated by immunohistochemical tests using Vimentin and S-100. This case highlights unusual presentation of myoepithelioma outside the parotid gland, emphasizing the importance of considering these tumors as differential diagnosis. Awareness of these atypical manifestations is crucial for accurate diagnosis and optimal patient management.